Banks As Coordinators of Economic Growth - Ueda, Kenichi (IMF Working Papers; Working Paper ;, 2006)
This paper formally identifies an important role of banks: Banks competitively internalize production externalities and facilitate economic growth. I formulate a canonical growth model with externalities as a game among consumers, firms, and banks. Banks compete for deposits to seek monopoly profits, including externalities. Using loan contracts that specify price and quantity, banks control firms' investments. Each bank forms a firm group endogenously and internalizes externalities directly within a firm group and indirectly across firm groups. This unique equilibrium requires a condition that separates competition for sources and uses of funds. I present a realistic institution that satisfies this condition.